SP0022 Prevention is Better than Cure: A New Dawn for the Management of RA?. (23rd January 2014) - Gerlag, D. M.
Abstract : Rheumatoid Arthritis (RA) is a prototype immune-mediated inflammatory disease, in which persistent inflammation leads to joint damage, with as a consequence disability, loss of quality of life, reduced ability to work and increased health care utilization. RA is still associated with long-term morbidity and early mortality despite major developments in antirheumatic therapy. Among the connective tissue diseases RA is the commonest and the most important in socio-economic terms. Because of the high impact of RA for the individual patient as well as society, and the fact that current treatment options are still not effective in reducing disease progression or bringing the disease in remission for most of the RA patients, the need for and interest in prevention of RA is rapidly growing. There are at present no interventions known to prevent the onset of the clinical manifestations of RA. The past few years, research in the field of RA has focused on the earliest stages of disease, leading to the discovery that circulating auto-antibodies, increased acute phase reactants, and possibly asymptomatic synovitis precede the clinical onset of the disease. Before the onset of any signs of arthritis, elevated levels of auto-antibodies like IgM-rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA) can be found in blood samples. These auto-antibodies may be present at a median of 5 years before clinical symptoms appear. Subjects with these auto-antibodies and arthralgia have a chance of 40-70% of developing RA within 5 years. Moreover, histological studies have shown all features of chronic synovial inflammation to be present in the earliest stages of the disease. Consistent with the notion that early arthritis represents chronic synovitis, a notable percentage of RA patients have signs of joint destruction at the time of initial diagnosis. These data form strong evidence that clinical signs and symptoms may be preceded by a pre-clinical phase for several years and that early RA (as defined at present clinically) in fact represents chronic synovitis. In RA chronic synovitis converses to autonomous disease progression by the induction of several mechanisms. Similar to the proliferation of a locally growing tumor, synovial tissue mass may increase over time, making successful treatment more difficult. In addition, secondary degradation of cartilage and bone may promote synovial inflammation, resulting in a vicious cycle. It is known that early in the course of disease a window of opportunity exists, during which the introduction of aggressive antirheumatic therapy can result in a change in the natural course of disease, leading to protection against joint destruction and prevention of disability. This concept can be brought to another level now we are able to identify those who are at risk of developing RA, by even earlier intervention, aiming at the prevention of the onset of clinical signs and symptoms of arthritis, preventing the need for chronic immunosuppressive therapy. At present, no interventions or therapies are known that would prevent the onset of clinical signs and symptoms associated with arthritis in RA patients. However, the immunological knowledge has advanced to a stage where such an intervention is likely to be successful. Prevention of RA by targeted intervention in subjects who are at high risk for the development of RA has been subject of study and has the intend to lay the basis for more preventive strategies in RA, which would represent a significant paradigm shift from chronic immunosuppressive treatment to prevention. Disclosure of Interest: None Declared